Insights into the microstructure evolution of slag, fly ash and condensed silica fume in blended cement paste. (22nd November 2021) - Li, Lihui; Yang, Jian; Li, Huanyu; Du, Yuhang
Highlights: Strip delineation method was performed on the BSE and EDS images to determine the inner product region of SCM particles. The inner products of fly ash and slag displayed higher Si/Ca and Al/Ca ratios the newly formed inner products of slag were relatively enriched in Mg. The presence of hydrating rims can trigger the microcrack propagation of silica fume agglomeration. The proposed BSE-EDS image analysis is applicable and effective for SCMs research at particle scale. Abstract: This study traces the spatial microstructure evolution and chemical changes of supplementary cementitious materials (SCMs) during the hydration process at the particle scale. Backscattered electron microscopy and energy-dispersive X-ray spectroscopy (BSE-EDS) techniques coupled with strip delineation image analysis are used to visualize and identify the phase assemblage in the particle region, inner product region and outer product region. The EDS mapping profiles change rapidly in the inner product region and stabilize in the outer product region, which is attributed to the migration of the ions dissolved from the SCMs. The inner products of fly ash and slag display higher Si/Ca and Al/Ca ratios than those in the outer products. It is worth noting that the Mg in the inner product region shows a similar concentration to that in the unreacted slag particle region. In addition, the newly formed C-S-H phase located in the reacting rims could trigger the microcrack within the silica fume agglomeration by inserting expansive forces.